Exploring the Effectiveness of Scratch Assisted Problem-Based Learning on Students’ Conceptual Understanding : A Quasi-Experimental Study - Devi Syafitri Padang; Eyus Sudihartinih (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
This study aims to analyze the effect of using Scratch-based Problem-Based Learning on junior high school students’ understanding of mathematical concepts in the topic of Systems of Linear Equations with Two Variables. This study employs a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 62 eighth-grade junior high school students, comprising 32 students in the experimental group and 30 students in the control group. The experimental group received instruction using the Scratch-based PBL approach, while the control group received conventional instruction. Data were collected through pre- and post-instruction tests of mathematical conceptual understanding and were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s test of homogeneity, the paired samples t-test, the independent samples t-test, Normalized Gain (N-Gain) analysis, and Cohen’s d effect size. The results of the study indicate that the use of Scratch-based Problem-Based Learning media led to a significantly higher improvement in mathematical conceptual understanding compared to conventional instruction. The experimental group achieved an average N-Gain of 0.589, which was higher than that of the control group, which achieved an average N-Gain of 0.352, with a statistically significant difference (p < 0.001). Furthermore, the analysis results showed an effect size (Cohen’s d) of 1.076, which falls into the “large” category, indicating that the implementation of Scratch-based Problem-Based Learning has a strong practical impact on improving students’ mathematical conceptual understanding. The novelty of this study lies in the integration of Scratch as a visual programming environment into every stage of Problem-Based Learning to facilitate the visualization, exploration, and reflection of mathematical concepts, thereby strengthening students’ knowledge construction process.